Does the Holiday Effect Differ from Religious to Non-Religious Holidays? Empirical Evidence from Egypt - Al-Ahmad, Zeina; Al-Ali, Suzan (The Economics and Finance Letters, 2016)
This study aims to investigate the presence of holiday effect on the Egyptian Exchange (EGX) over the period 2010 to 2015. It utilizes daily data of the EGX30 index prices and trading volumes and applies dummy variables OLS regression. Three types of holidays are examined those being, secular, Islamic, and Christian, and those, in turn, are disaggregated into their individual components. The findings reveal that there are differences in the behavior of stock prices between holidays. While the secular and Islamic holidays are mainly associated with positive pre-holiday returns, the Christian holidays are associated with positive post-holiday returns. Disaggregating these holidays into their individual components reveals that the Police Day holiday, Eid Al-Fitr holiday and Eastern Christmas holiday are the major holidays driving the secular, Islamic and Christian holidays’ effect respectively. Interestingly, the results obtained when the trading volume is used do not support the presence of a holiday effect on trading volume. The findings could have important implications for developing profitable investment strategies in periods of holidays.